Rare coexistence of psoriasis, lichen sclerosus and morphea – case report and literature data - Baran, Anna; Flisiak, Iwona; Chodynicka, Bożena (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction. Psoriasis is a chronic and recurrent skin disease, affecting 2-3% of the population. Emotional distress, infections and mechanical trauma are well known precipitating factors. Association between psoriasis and other systemic diseases, i.e. obesity or diabetes mellitus was reported. In the literature there are a few reports about coexistence of psoriasis with other skin diseases, especially with scleroderma and lichen sclerosus. Objective. The aim of this paper was to present a patient with 5-year- history of psoriasis and 3-year-history of lichen sclerosus in whom, during the hospitalization additionally morphea was diagnosed. Case report . We present a case of 61-year-old woman in whom after cardiac valvuloplastic surgery first psoriatic lesions on the skin of scalp, trunk and lower and upper extremities occurred. Two years later porcelain-white papules, forming bigger, a bit indurated plaques affecting the vulva and perineum were noticed. The biopsy from vulvar lesions confirmed the diagnosis of lichen sclerosus. The patient did not report any other symptoms and was treated with metronidasole cream and corticosteroid ointment. During the hospitalization the foci of slightly indurated hiperpigmentation on the skin of abdomen lasting for over 20 years were noticed. The clinical picture and skin biopsy were consistent with morphea. Conclusions . Although psoriasis, scleroderma and lichen sclerosus are quite common in the population, there are only a few reports on the coexistence of all these diseases. Mechanical trauma as a provoking factor of psoriasis, lichen sclerosus and morphea was reported. In presented case cardiac surgery could be one of factors triggering appearance of skin lesions. There are assumptions that psoriasis in morphea patients may be regarded as a bad prognostic sign of possible transition of morphea into progressive systemic scleroderma. The patient requires detailed diagnostic procedures and treatment in dermatological and rheumatologic units.